Production risk, technical efficiency, and input use nexus: Lessons from Bangladesh aquaculture - Md. Akhtaruzzaman Khan; RatnaBegum; RasmusNielsen; Ayoe Hoff (Wiley, 2025)
The optimal use of resources in aquaculture is important, especially in developing countries, to obtain the highest possible outcome from the production process to support food security and poverty alleviation. Thus, within this study, the risk, efficiency, and input-use variation in aquaculture farms in Bangladesh is investigated using a flexible stochastic frontier model with a risk and an inefficiency function. The results reveal that feed, labor, and capital have positive and significant impacts on production. In addition, an increased fingerling density and a larger farm increase the risk, whereas the use of feed and the capital invested have the opposite effect. Access to extension services has a positive effect and increases farm efficiency. An investigation of the farm size–productivity inverse relationship reveals that this phenomenon is not applicable to Bangladesh aquaculture. In general, efficient farmers are large-scale farmers, who use a lower stocking density but a higher feeding intensity, resulting in a higher yield. On average, farmers use less labor and feed than what is optimal. To increase efficiency and reduce risk, it is recommended that more technical knowledge on optimal input use, extension service, and capital is made available to aquaculture farmers.